Indonesian Baha’i Community’s Perspective on Gender Equality - Hidayat, Samsul (Al-Albab, 2023)
The conception of gender for Indonesian context is understood socially, politically, culturally and even religiously biased. Gender equality, which is always regarded as respect for women, is actually a detrimental action for women themselves. This work seeks to explain the concept of gender equality in Indonesian context from the perspective of the Baha’i faith and find out the views of its followers about the role of women in gender equality. This is also to describe the principles of the teachings of the Baha’i faith in promoting the awareness of women’s equal role in Indonesia. The article is based on research that falls under the descriptive qualitative research cluster using a gender study approach. The data were collected using observation, in-depth interviews and sources from previous studies. The work suggests that the followers of the Baha’i faith view the differences between men and women only from biological factors that exist in both sexualities. Those differences are merely due to the cultures of the people so that the understanding about gender equality becomes a biased concept. This is because the people in Indonesia observe to a patriarchal ideology which considers men to be superior and versatile while women are weak and marginalized in terms of social situation. The Baha’i community believe that God create humans from the same source, namely dust, so that no humans would exalt over the others. Humans are the same and equal between men and women.